(untitled) (International journal of artificial intelligence, 2026)
This article discusses the role and importance of innovative educational models in the formation of national values ​​and patriotism in young people, improving the educational process based on modern pedagogical approaches, developing social activism, national pride and civic responsibility in students, methods of introducing innovative educational models into the pedagogical system, mechanisms for increasing their effectiveness, and ways to put them into practice.